Patterns of Wnt signaling in the life cycle of Podocoryna carnea and its implications for medusae evolution in Hydrozoa (Cnidaria). Issue 6 (21st October 2015) - Sanders, Steven M.; Cartwright, Paulyn
SUMMARY Hydrozoans are known for their complex life cycles, alternating between benthic, asexually reproducing polyps and pelagic, sexually reproducing medusae. Although patterning in hydrozoan polyps has been well studied, little is known about the signaling mechanisms governing medusa development. In order to investigate the role of Wnt signaling in medusa development, we use RNA‐Seq data collected from three discrete life cycle stages of Podocoryna carnea to assemble, annotate, and assess enrichment and differential expression (DE) of Wnt pathway elements in P. carnea's transcriptome. Enrichment analyses revealed a statistically significant enrichment of DE Wnt signaling transcripts in the transcriptome of P. carnea, of which, the vast majority of these were significantly up‐regulated in developing and adult medusae stages. Whole mount in situ hybridization (ISH) reveals co‐expression of the Wnt ligand, Wnt3, and a membrane bound Wnt receptor, frizzled3, at the distal and oral ends of the developmental axes of medusae and polyps in P. carnea. DE and ISH results presented here reveal expression of Wnt signaling components consistent with it playing a role in medusa development. Specifically, Wnt ligand expression in the oral region suggests that the Wnt pathway may play a role in medusa patterning, similar to that of polyps. Previous Wnt expression studies in hydrozoan taxa with reduced medusa have failed to detect co‐expression of Wnt3 and a frizzled receptor at their truncated developmental axes, suggesting that down regulation of Wnt pathway elements may play a key role in the loss of the medusa life cycle stage in hydrozoan evolution.